Super-hydrophobic nanofiber composite membrane with gradient structure as well as preparation method and application of super-hydrophobic nanofiber composite membrane

By using a superhydrophobic nanofiber composite membrane with a gradient structure, the problems of oil-water separation membrane pollution and reduced separation efficiency in the existing technology are solved, and efficient and stable water-in-oil emulsion separation is achieved.

CN119303456APending Publication Date: 2025-01-14NINGBO PROD & FOOD QUALITY INSPECTION INST (NINGBO FIBER INSPECTION INST)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411684798.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing oil-water separation membranes are prone to contamination when treating water-in-oil emulsions containing surfactants, and the separation efficiency of the membrane decreases after increasing the driving pressure, and the service life is short.

Method used

A superhydrophobic nanofiber composite membrane with a gradient structure is used. The membrane is composed of a support layer and a gradient hydrophobic layer. The gradient hydrophobic layer uses zinc oxide nanowires and is prepared through techniques such as counter-jet electrospinning, hydrothermal synthesis and fluorination treatment.

Benefits of technology

It improves the anti-fouling and high permeability of the membrane, extends the service life of the membrane, and shows excellent cycle stability and high separation efficiency in water-in-oil emulsion separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303456A_ABST
    Figure CN119303456A_ABST
Patent Text Reader

Abstract

The invention relates to a super-hydrophobic nanofiber composite membrane with a gradient structure and a preparation method and application of the super-hydrophobic nanofiber composite membrane, the super-hydrophobic nanofiber composite membrane comprises a supporting layer and a gradient hydrophobic layer, and the gradient hydrophobic layer is made of zinc oxide nanowires. The nanofiber composite membrane has pollution resistance and high permeability, and has excellent cycle stability in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of emulsion separation, and in particular to a super-hydrophobic nanofiber composite membrane with a gradient structure, and a preparation method and application thereof. Background Art

[0002] Oil is an important non-renewable energy source. The large amount of oil-water emulsion produced in the chemical industry, crude oil extraction, mechanical processing and food processing is directly discharged without treatment, which not only causes serious harm to the ecological environment, but also causes huge economic losses. Therefore, the effective removal of water in oil is of great significance to alleviate the energy crisis and protect the ecological environment.

[0003] Oil-water separation technologies include chemical methods, biological methods, centrifugal methods and membrane separation methods. Among them, membrane separation technology is considered to be a new and efficient oil-water mixture purification technology due to its advantages of low cost, simple operation and high separation efficiency. Membrane separation is the process of selectively separating oil-water mixtures using special wettability membranes driven by gravity or external pressure. Usually, the preparation methods of separation membranes mainly include vacuum-assisted filtration, melt spinning, phase separation and electrospinning. At present, electrospun nanofiber membranes with different wettabilities have attracted widespread attention in the field of oil-water separation due to their high porosity, internal and external through-hole structure, and high specific surface area. However, for oil-in-water emulsions containing surfactants, the membrane is easily attached by the surfactant, causing membrane fouling. In order to solve the problem of membrane fouling, many researchers have proposed to design superhydrophobic surfaces to enhance the membrane's repulsion to water droplets, thereby improving the membrane's anti-fouling properties.

[0004] At the same time, the driving pressure will be introduced to obtain higher flux under increasing environmental pressure, which will cause sliding between the fibers in the membrane and produce larger pores, resulting in a decrease in the separation efficiency of the membrane. Therefore, inventing an efficient and high-flux nanofiber composite membrane is crucial to extend the service life of the separation membrane. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a super-hydrophobic nanofiber composite membrane with a gradient structure and a preparation method and application thereof. The nanofiber composite membrane has anti-pollution and high permeability, and thus has excellent cycle stability in practical applications.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a super-hydrophobic nanofiber composite membrane with a gradient structure, wherein the super-hydrophobic nanofiber composite membrane comprises a support layer and a gradient hydrophobic layer, wherein the material of the gradient hydrophobic layer is zinc oxide nanowires.

[0008] In the present invention, the material of the gradient hydrophobic layer is zinc oxide nanowires, which are connected to the support layer. Since the density and length of the zinc oxide nanowires at different positions are different, more pores are formed in the gradient hydrophobic layer. The closer to the support layer, the larger the pore size. The farther away from the support layer, the larger the density of the zinc oxide nanowires, and the longer the length, thereby forming a gradient structure, which can prevent small droplets from penetrating, thereby improving the separation efficiency. That is, the structure of the gradient hydrophobic layer is that the closer to the support layer, the larger the pore size.

[0009] Preferably, the minimum pore size of the gradient hydrophobic layer is 0.3-0.6 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm or 0.6 μm.

[0010] Preferably, the material of the support layer is any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polystyrene or polysulfone, or a combination of at least two thereof.

[0011] Preferably, the hydroxyl groups on the surface of the zinc oxide nanowires are -OSiC8H4F 13 replace;.

[0012] The formation of hydroxyl groups on the surface of zinc oxide is mainly due to the physical or chemical adsorption of water molecules by zinc oxide, and the adsorbed water molecules dissociate to form hydroxyl groups, which combine with zinc atoms in zinc oxide to form hydroxyl groups. In the present invention, the hydroxyl groups on the surface of zinc oxide nanowires are fluorinated to make the nanofiber composite membrane super hydrophobic.

[0013] Preferably, the thickness of the super-hydrophobic nanofiber composite membrane with a gradient structure is 50-80 μm, for example, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm or 80 μm.

[0014] In a second aspect, the present invention provides a method for preparing a super-hydrophobic nanofiber composite membrane with a gradient structure according to the first aspect, the preparation method comprising dissolving the material of the support layer and zinc acetate, dissolving the water-soluble polymer and then using a counter-jet electrospinning technology to obtain a nanofiber membrane, which is obtained after heat treatment, hydrothermal synthesis and fluorination treatment.

[0015] In the traditional preparation method, since the support layer is a hydrophobic polymer, during hydrothermal growth, the support layer will float in the solution because its density is lower than that of the growth solution, and only the surface layer in contact with the solution can grow zinc oxide nanowires.

[0016] In the present invention, the creative addition of water-soluble polymers in the preparation of nanofiber composite membranes can significantly increase the contact area between the support layer and the growth solution. Due to its water-soluble properties, the water-soluble polymer can promote the contact area between the hydrophobic support layer and the growth solution, which will cause the zinc oxide nuclei on the surface of the nanofiber membrane to contact more with the growth solution, and the zinc oxide nanowires grown on the surface of the membrane will be longer and denser, forming a smaller pore size, preventing small droplets from penetrating, thereby improving the separation efficiency; while the nanofiber surface with less contact with the growth solution inside the membrane will grow sparse and shorter zinc oxide nanowires, which will gradually increase the pore size inside the membrane. In the hydrothermal synthesis step, the water-soluble polymer can be removed to further increase the porosity of the membrane.

[0017] Preferably, the preparation method of the nanofiber membrane includes: adding the material of the support layer and zinc acetate to an N,N-dimethylformamide solution, performing a first stirring to obtain a solution A, dissolving a water-soluble polymer with deionized water, performing a second stirring to obtain a solution B, and spinning solution A and solution B by spray electrospinning to obtain a nanofiber membrane.

[0018] Preferably, the water-soluble polymer includes any one of polyvinyl alcohol, polyethylene glycol, polyacrylamide or polyvinyl pyrrolidone, or a combination of at least two thereof.

[0019] Preferably, the electrospinning time is 1-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0020] Preferably, the mass ratio of zinc acetate to the material of the support layer in the solution A is (5-15): 100. The 5-15 may be, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, etc.

[0021] Preferably, the mass concentration of the material of the support layer in the solution A is 7-13%, for example, 7%, 8%, 9%, 10%, 11%, 12% or 13%.

[0022] Preferably, the mass concentration of the water-soluble polymer in the solution B is 5-11%, for example, 5%, 6%, 7%, 8%, 9%, 10% or 11%.

[0023] Preferably, the heat treatment temperature is 100-150°C, and the time is 10-24h. The 100-150°C may be, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C. The 10-24h may be, for example, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h.

[0024] Preferably, the hydrothermal synthesis comprises the following steps: placing the nanofiber membrane in a growth solution for hydrothermal synthesis to obtain a gradient nanofiber membrane.

[0025] Preferably, the growth solution comprises hexamethylenetetramine, zinc chloride and ammonia water.

[0026] Preferably, the concentration of the hexamethylenetetramine is 0.1-0.5 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L.

[0027] Preferably, the concentration of zinc chloride is 0.1-1.5 mol / L, for example, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L or 1.5 mol / L, etc.

[0028] Preferably, the concentration of the ammonia water is 2-5%, for example, 2%, 3%, 4% or 5%.

[0029] Preferably, the temperature of the hydrothermal synthesis is 90-100°C, and the time is 2-4h. The 90-100°C may be, for example, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, etc. The 2-4h may be, for example, 2h, 2.5h, 3h, 3.5h or 3h, etc.

[0030] Preferably, the fluorination treatment comprises the following steps: placing a gradient nanofiber membrane above a fluorinating agent and a solvent, and using chemical vapor deposition to obtain a super-hydrophobic nanofiber composite membrane with a gradient structure.

[0031] Preferably, the fluorinating agent comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane and / or heptadecafluorodecyltrimethoxysilane.

[0032] Preferably, the solvent comprises anhydrous ethanol and / or isopropanol.

[0033] Preferably, the mass concentration of the fluorinating agent is 2-5%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0034] Preferably, the chemical vapor deposition process temperature is 50-85°C, and the process time is 3-12h. The 50-85°C may be, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C, etc. The 3-12h may be, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.

[0035] In a third aspect, the present invention provides a use of the super-hydrophobic nanofiber composite membrane with a gradient structure according to the first aspect in separation of water-in-oil emulsions.

[0036] Preferably, the particle size of the water-in-oil emulsion is 1014-1482 nm, for example, it may be 1014 nm, 1050 nm, 1100 nm, 1150 nm, 1200 nm, 1250 nm, 1300 nm, 1350 nm, 1400 nm, 1450 nm or 1482 nm.

[0037] Compared with the prior art, the present invention has at least the following beneficial effects:

[0038] 1. The introduction of water-soluble polyvinyl alcohol nanofibers in the spray electrospinning technology increases the contact area and immersion depth of the subsequent nanofiber membrane with the growth solution.

[0039] 2. During the hydrothermal synthesis of zinc oxide nanowires, due to the presence of polyvinyl alcohol nanofibers, the zinc oxide nuclei on the surface of the nanofiber membrane will be in more contact with the growth liquid, and the zinc oxide nanowires grown on the membrane surface will be longer and denser, forming smaller pores, preventing small droplets from passing through, thereby improving the separation efficiency; while the sparse and shorter zinc oxide nanowires grow on the surface of the nanofibers inside the membrane that have less contact with the growth liquid, which will gradually increase the pore size inside the membrane; at the same time, the water-soluble polyvinyl alcohol nanofibers are removed during the hydrothermal process, which increases the porosity of the membrane and provides a wider permeation channel, thereby increasing the permeation flux of the membrane.

[0040] 3. The hydroxyl groups of zinc oxide nanowires were fluorinated with 1H, 2H, 2H-perfluorooctyltriethoxysilane by chemical vapor deposition, so that the nanofiber composite membrane had superhydrophobicity.

[0041] 4. Superhydrophobic zinc oxide@polyvinylidene fluoride nanofiber composite membrane is used to separate oil-in-water emulsion containing surfactant. Its gradient pore structure can improve the separation efficiency, improve the liquid permeability, and improve the anti-fouling property, so that it has good cyclic stability when separating oil-in-water emulsion. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a scanning electron microscope schematic diagram of the top surface of the gradient structure zinc oxide@polyvinylidene fluoride nanocomposite membrane in Example 2.

[0043] Figure 2 This is a scanning electron microscope schematic diagram of the bottom surface of the gradient structure zinc oxide@polyvinylidene fluoride nanocomposite membrane in Example 2.

[0044] Figure 3 This is a scanning electron microscope schematic diagram of the cross-section of the gradient structure zinc oxide@polyvinylidene fluoride nanocomposite membrane of Example 2.

[0045] Figure 4 This is a schematic diagram of a scanning electron microscope showing the top surface of the zinc oxide@polyvinylidene fluoride nanocomposite film of comparative example 1.

[0046] Figure 5 This is a schematic diagram of a scanning electron microscope showing the bottom surface of the zinc oxide@polyvinylidene fluoride nanocomposite film of comparative example 1.

[0047] Figure 6 This is a schematic diagram of a scanning electron microscope cross section of the zinc oxide@polyvinylidene fluoride nanocomposite film of comparative example 1.

[0048] Figure 7 This is a schematic diagram of a scanning electron microscope showing the top surface of the zinc oxide@polyvinylidene fluoride nanocomposite film of comparative example 2.

[0049] Figure 8 This is a schematic diagram of a scanning electron microscope showing the bottom surface of the zinc oxide@polyvinylidene fluoride nanocomposite film of comparative example 2.

[0050] Fig. 9 This is a schematic diagram of a scanning electron microscope cross section of the zinc oxide@polyvinylidene fluoride nanocomposite film of comparative example 2.

[0051] Fig.10 This is a diagram of the water contact angle on the top surface of the gradient structure zinc oxide@polyvinylidene fluoride nanocomposite film of Example 2.

[0052] Fig.11 This is a real picture of Example 2 before and after the gradient structure zinc oxide @ polyvinylidene fluoride nanocomposite membrane separates the diesel water-in-water emulsion stabilized by Span 80 with an average particle size of 1482 nm.

[0053] Fig.12 This is a graph showing the result of ten cycles of the gradient structure zinc oxide-polyvinylidene fluoride nanocomposite membrane of Example 2 on a diesel water-in-water emulsion containing Span 80 with an average particle size of 1014 nm. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0055] Example 1

[0056] This example prepares a super-hydrophobic nanofiber composite membrane with a gradient structure

[0057] (1) Preparation of polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane

[0058] Add polyvinylidene fluoride (PVDF) powder and zinc acetate to N, N-dimethylformamide solution, and stir at 25°C to achieve complete dissolution to obtain solution A; add polyvinyl alcohol (PVA) powder to deionized water, and stir at 25°C to dissolve the PVA powder to obtain solution B; then spin solution A and solution B by counter-electrospinning technology to obtain polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane, the mass ratio of zinc acetate to the material of the support layer in solution A is 10:100, the concentration of PVDF is 10%, the concentration of PVA is 7%, and the spinning time of the PVA solution is 1h.

[0059] (2) Heat treatment

[0060] The polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane was placed in an oven for heat treatment at a temperature of 150° C. for 10 h.

[0061] (3) Hydrothermal reaction

[0062] The polyvinylidene fluoride / polyvinyl alcohol / zinc oxide nanofiber membrane was placed in a growth solution of hexamethylenetetramine, zinc chloride and ammonia water to obtain a gradient structure zinc oxide@polyvinylidene fluoride nanofiber composite membrane. The concentration of hexamethylenetetramine was 0.1 mol / L, the concentration of zinc chloride was 0.2 mol / L, the concentration of ammonia water was 4%, the hydrothermal synthesis temperature was 95°C, and the hydrothermal synthesis time was 2 h.

[0063] (4) Fluoridation

[0064] The zinc oxide @ polyvinylidene fluoride nanofiber composite membrane is placed on top of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and anhydrous ethanol solution, and the zinc oxide @ polyvinylidene fluoride nanofiber composite membrane is modified by chemical vapor deposition technology to obtain a hydrophobic zinc oxide @ polyvinylidene fluoride nanofiber composite membrane, wherein the mass fraction of the 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is 2%, the treatment temperature is 85°C, and the time is 3h.

[0065] Example 2

[0066] This example prepares a super-hydrophobic nanofiber composite membrane with a gradient structure

[0067] (1) Preparation of polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane

[0068] Add polyvinylidene fluoride (PVDF) powder and zinc acetate to N,N-dimethylformamide solution, and stir at 20°C to achieve complete dissolution to obtain solution A; add polyvinyl alcohol (PVA) powder to deionized water, and stir at 30°C to dissolve the PVA powder to obtain solution B; then, spin solution A and solution B by counter-electrospinning technology to obtain polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane, the mass ratio of zinc acetate to the material of the support layer in solution A is 15:100, the concentration of PVDF is 13%, the concentration of PVA is 11%, and the spinning time of the PVA solution is 2h.

[0069] (2) Heat treatment

[0070] The polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane was placed in an oven for heat treatment at a temperature of 130° C. for 12 h.

[0071] (3) Hydrothermal reaction

[0072] The polyvinylidene fluoride / polyvinyl alcohol / zinc oxide nanofiber membrane was placed in a growth solution of hexamethylenetetramine, zinc chloride and ammonia water to obtain a gradient structure zinc oxide@polyvinylidene fluoride nanofiber composite membrane. The concentration of hexamethylenetetramine was 0.1 mol / L, the concentration of zinc chloride was 0.1 mol / L, the concentration of ammonia water was 5%, the hydrothermal synthesis temperature was 90°C, and the hydrothermal synthesis time was 3 h.

[0073] (4) Fluoridation

[0074] The zinc oxide @ polyvinylidene fluoride nanofiber composite membrane is placed on top of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and anhydrous ethanol solution, and the zinc oxide @ polyvinylidene fluoride nanofiber composite membrane is modified by chemical vapor deposition technology to obtain a superhydrophobic zinc oxide @ polyvinylidene fluoride nanofiber composite membrane, wherein the mass fraction of the 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is 2%, the treatment temperature is 60°C, and the time is 8h.

[0075] Example 3

[0076] This example prepares a super-hydrophobic nanofiber composite membrane with a gradient structure

[0077] (1) Preparation of polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane

[0078] Add polyvinylidene fluoride (PVDF) powder and zinc acetate to N,N-dimethylformamide solution, and stir at 30°C to achieve complete dissolution to obtain solution A; add polyvinyl alcohol (PVA) powder to deionized water, and stir at 20°C to dissolve the PVA powder to obtain solution B; then spin solution A and solution B by counter-electrospinning technology to obtain polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane, the mass ratio of zinc acetate to the material of the support layer in solution A is 10:100, the concentration of PVDF is 7%, the concentration of PVA is 5%, and the spinning time of the PVA solution is 3h.

[0079] (2) Heat treatment

[0080] The polyvinylidene fluoride / polyvinyl alcohol / zinc acetate nanofiber membrane was placed in an oven for heat treatment at a temperature of 100° C. for 24 hours.

[0081] (3) Hydrothermal reaction

[0082] The polyvinylidene fluoride / polyvinyl alcohol / zinc oxide nanofiber membrane was placed in a growth solution of hexamethylenetetramine, zinc chloride and ammonia water to obtain a gradient structure zinc oxide@polyvinylidene fluoride nanofiber composite membrane. The concentration of hexamethylenetetramine was 0.2 mol / L, the concentration of zinc chloride was 0.3 mol / L, the concentration of ammonia water was 3%, the hydrothermal synthesis temperature was 100°C, and the hydrothermal synthesis time was 2 h.

[0083] (4) Fluoridation

[0084] The zinc oxide @ polyvinylidene fluoride nanofiber composite membrane is placed on top of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and anhydrous ethanol solution, and the zinc oxide @ polyvinylidene fluoride nanofiber composite membrane is modified by chemical vapor deposition technology to obtain a superhydrophobic zinc oxide @ polyvinylidene fluoride nanofiber composite membrane, wherein the mass fraction of the 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is 3%, the treatment temperature is 70°C, and the time is 5h.

[0085] Comparative Example 1

[0086] In this comparative example, a super-hydrophobic nanofiber composite membrane with a gradient structure is prepared. The preparation method thereof is different from that of Example 1 only in that polyvinyl alcohol is not added, and the rest is the same as that of Example 1.

[0087] Comparative Example 2

[0088] This comparative example prepares a super-hydrophobic nanofiber composite membrane, and the specific preparation method is as follows:

[0089] (1) Preparation of polyvinylidene fluoride / zinc acetate nanofiber membrane

[0090] Polyvinylidene fluoride (PVDF) powder and zinc acetate are added to N,N-dimethylformamide solution and stirred at 30°C to achieve complete dissolution; the above solution is spun by electrospinning technology to obtain a polyvinylidene fluoride / zinc acetate nanofiber membrane, wherein the mass ratio of zinc acetate to PVDF powder is 15:100, and the concentration of PVDF is 13%.

[0091] (2) Heat treatment

[0092] The polyvinylidene fluoride / zinc acetate nanofiber membrane was placed in an oven for heat treatment at a temperature of 130° C. for 12 h.

[0093] (3) Hydrothermal reaction

[0094] The polyvinylidene fluoride / zinc oxide nanofiber membrane was soaked in anhydrous ethanol for 10 minutes, and then placed in a growth solution of hexamethylenetetramine, zinc chloride and ammonia water to obtain a zinc oxide@polyvinylidene fluoride nanofiber composite membrane. The concentration of hexamethylenetetramine was 0.1 mol / L, the concentration of zinc chloride was 0.1 mol / L, the concentration of ammonia water was 5%, the hydrothermal synthesis temperature was 95°C, and the hydrothermal synthesis time was 3 h.

[0095] (4) Fluoridation

[0096] The zinc oxide @ polyvinylidene fluoride nanofiber composite membrane was placed on top of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and anhydrous ethanol solution, and the zinc oxide @ polyvinylidene fluoride nanofiber composite membrane was modified by chemical vapor deposition technology to obtain a superhydrophobic zinc oxide @ polyvinylidene fluoride nanofiber composite membrane, wherein the mass fraction of the 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane was 3%, the treatment temperature was 55°C, and the time was 9h.

[0097] Test Example 1

[0098] In this example, the structure of the prepared nanofiber membrane was analyzed.

[0099] In this example, the nanofiber membrane prepared in Example 2 was analyzed by scanning electron microscopy. The results show that: Figure 1 and Figure 2 The top and bottom surfaces of the super-hydrophobic nanofiber composite membrane with a gradient structure are shown in the SEM diagram. The top surface of the nanofiber membrane prepared in the present invention is in contact with more growth solution, and the zinc oxide nanowires are long and dense, while the bottom surface is not in contact with the growth solution and has no zinc oxide nanowires and is still a nanofiber. Figure 3 In the schematic diagram of the cross section, it can be clearly seen that the pore size gradually increases from top to bottom. Fig.10 It can be seen that the surface water contact angle of Example 2 is 151°, and the film has superhydrophobicity.

[0100] Figure 4-6 This is a scanning electron microscope image of a nanofiber composite membrane without a water-soluble polymer in Comparative Example 1. Figure 4 It can be seen that the surface of the nanofibers is completely covered by zinc oxide nanowires. Figure 5 The bottom surface of the membrane is still nanofibers. This is because the hydrophobic nanofiber membrane has a density lower than that of water and floats on the growth liquid, with only one side in contact with the growth liquid. Figure 6 In the cross-sectional schematic diagram, it can be clearly seen that zinc oxide nanowires only grow on the membrane surface and no gradient pore structure is formed.

[0101] Figure 7-9 This is a scanning electron microscope image of the nanofiber composite membrane treated with ethanol in Comparative Example 2. Figure 7 It can be seen that ZnO nanowires have not grown on some nanofibers, and ZnO nanowires have not completely covered the nanofibers, forming larger pores. Figure 8 Zinc oxide nanowires also grow on the nanofibers on the bottom of the membrane. This is because the nanofiber membrane is hydrophilic after being wetted with ethanol and the membrane is immersed in the growth liquid during hydrothermal growth. Fig. 9 From the cross-sectional schematic diagram, it can be seen that zinc oxide nanowires are grown all over the inside and surface of the membrane.

[0102] Test Example 2

[0103] This test example tests the separation performance of water-in-oil emulsion.

[0104] The nanofiber composite membranes prepared in the above Examples 1-3 and Comparative Examples 1-2 were used to separate Span 80-stabilized diesel water-in-water emulsions with an average particle size of 1482 nm. The specific steps of preparing the emulsion are as follows: Span 80 was added to deionized water and mixed with diesel, and stirred at 7500 r / min under a high-speed homogenizer to obtain a uniform emulsion with an average particle size of 1482 nm. The water-oil volume ratio was 1:99, and the Span 80 concentration was 0.4 g L -1 The obtained emulsion was filtered by a cross-flow filtration device, with the side where zinc oxide was grown in contact with the emulsion, and clear and transparent diesel was obtained after separation. The specific results are shown in Table 1:

[0105] Table 1

[0106]

[0107] The results show that: as shown in Table 1 and Fig.11 As shown, the gradient structure zinc oxide @ polyvinylidene fluoride nanofiber membrane prepared by the present invention is used to separate oil-in-water emulsion containing surfactant. Compared with comparative examples 1 and 2, it shows high separation efficiency for small particle size droplets, and has super hydrophobicity and anti-pollution properties, which is conducive to long-term stable filtration.

[0108] Test Example 3

[0109] This test example is used for particle size screening.

[0110] In this test example, the super-hydrophobic nanofiber composite membrane with a gradient structure prepared in Example 2 was used to filter the emulsion particle size test. The emulsion was ultrasonically cleaned for 30 minutes using Example 2 to obtain a uniform emulsion with an average particle size of 1209 nm. The water-oil volume ratio was 1:99, and the Span 80 concentration was 0.4 g L -1 The obtained emulsion was filtered by using a cross-flow device with the side where zinc oxide was grown in contact with the emulsion. After separation, clear and transparent diesel was obtained. The average particle size of the emulsion after separation was 932nm, the efficiency was 96.08%, and the flux was 1273.8L m -2 h -1 .

[0111] The gradient structure super-hydrophobic nanofiber composite membrane prepared in Example 2 was ultrasonically cleaned for 40 minutes to obtain a uniform emulsion with an average particle size of 1014 nm for separation. The water-oil volume ratio was 1:99, and the Span 80 concentration was 0.4 g / L -1 The obtained emulsion was filtered by using a cross-flow device with the side where zinc oxide was grown in contact with the emulsion. After separation, clear and transparent diesel was obtained. The average particle size of the emulsion after separation was 836nm, the efficiency was 94.7%, and the flux was 916.9L m -2 h -1 .

[0112] Test Example 4

[0113] This test case performs cyclic stability testing.

[0114] In this test example, the stability of the super-hydrophobic nanofiber composite membrane with a gradient structure prepared in Example 2 was tested. The uniform emulsion separation detection method with an average particle size of 1014 nm was used in Example 2, and the cycle was repeated 10 times, and the separation efficiency and flux of each time were analyzed.

[0115] pass Fig.12 It can be seen that after ten cycles, the separation efficiency is 91.7% and the flux is 603.4 L m -2 h -1 , and the separation efficiency and flux of each cycle are relatively stable, maintaining a high separation efficiency, which proves that the super-hydrophobic nanofiber composite membrane with a gradient structure of the present invention has high stability.

[0116] In summary, the present invention provides a super-hydrophobic nanofiber composite membrane with a gradient structure and a preparation method and application thereof. The nanofiber composite membrane has anti-pollution and high permeability, and thus has excellent cycle stability in practical applications.

[0117] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A super-hydrophobic nanofiber composite membrane with a gradient structure, characterized in that: The super-hydrophobic nanofiber composite membrane comprises a supporting layer and a gradient hydrophobic layer, and the material of the gradient hydrophobic layer is zinc oxide nanowires.

2. The super-hydrophobic nanofiber composite membrane with a gradient structure according to claim 1, characterized in that: The minimum pore size of the gradient hydrophobic layer is 0.3-0.6 μm.

3. The super-hydrophobic nanofiber composite membrane with a gradient structure according to claim 1 or 2, characterized in that: The material of the support layer is any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polystyrene or polysulfone, or a combination of at least two thereof.

4. The super-hydrophobic nanofiber composite membrane with a gradient structure according to any one of claims 1 to 3, characterized in that: The hydroxyl groups on the surface of the zinc oxide nanowires are 13 replace; Preferably, the thickness of the super-hydrophobic nanofiber composite membrane with a gradient structure is 50-80 μm.

5. A method for preparing a super-hydrophobic nanofiber composite membrane with a gradient structure according to any one of claims 1 to 4, characterized in that: The preparation method comprises dissolving the material of the support layer and zinc acetate, dissolving the water-soluble polymer, and then adopting the jet electrostatic spinning technology to obtain the nanofiber membrane, which is obtained after heat treatment, hydrothermal synthesis and fluorination treatment.

6. The preparation method according to claim 5, characterized in that: The preparation method of the nanofiber membrane comprises: adding the material of the support layer and zinc acetate into an N,N-dimethylformamide solution, performing a first stirring to obtain a solution A, dissolving a water-soluble polymer with deionized water, performing a second stirring to obtain a solution B, and spinning the solution A and the solution B by jet electrospinning to obtain a nanofiber membrane; Preferably, the water-soluble polymer includes any one or a combination of at least two of polyvinyl alcohol, polyethylene glycol, polyacrylamide or polyvinyl pyrrolidone; Preferably, the electrospinning time is 1-3 hours.

7. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of zinc acetate to the material of the support layer in the solution A is (5-15):100; Preferably, the mass concentration of the material of the support layer in the solution A is 7-13%; Preferably, the mass concentration of the water-soluble polymer in the solution B is 5-11%; Preferably, the heat treatment is carried out at a temperature of 100-150°C and for a time of 10-24 hours.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The hydrothermal synthesis comprises the following steps: placing the nanofiber membrane in a growth solution for hydrothermal synthesis to obtain a gradient nanofiber membrane; Preferably, the concentration of the hexamethylenetetramine is 0.1-0.5 mol / L; Preferably, the concentration of zinc chloride is 0.1-1.5 mol / L; Preferably, the concentration of the aqueous ammonia is 2-5%; Preferably, the hydrothermal synthesis is carried out at a temperature of 90-100° C. and for a time of 2-4 hours.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The fluorination treatment comprises the following steps: placing a gradient nanofiber membrane on top of a fluorinating agent and a solvent, and using chemical vapor deposition to obtain a super-hydrophobic nanofiber composite membrane with a gradient structure; Preferably, the fluorinating agent comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane and / or heptadecafluorodecyltrimethoxysilane; Preferably, the solvent comprises anhydrous ethanol and / or isopropanol; Preferably, the mass concentration of the fluorinating agent is 2-5%; Preferably, the chemical vapor deposition process is carried out at a temperature of 50-85° C. and a process time of 3-12 h.

10. Use of a super-hydrophobic nanofiber composite membrane with a gradient structure according to any one of claims 1 to 4 in separation of water-in-oil emulsions; Preferably, the particle size of the water-in-oil emulsion is 1014-1482 nm.

Citation Information

Cited By

  • Treatment process for separating oil emulsion wastewater in copper cable processing industry based on fiber membrane

    CN120364884A